Qualitative analysis of cyclamate in iced tea using varying BaCl2 concentrations: A descriptive study in sekaran raya - Aryati, Nur Indah; Ariyanti, Diva Fitria; Yolanda, Helen; Sa’diyah, Chalimatus; Amelia, Rizki Nor (Arfak Chem: Chemistry Education Journal, 2025)
Cyclamate is one type of artificial sweetener that is widely used in beverages. However, excessive consumption can hurt health. This study aims to determine the presence of cyclamate content in iced tea products sold in the Sekaran Raya area around the campus of Semarang State University. The method used was descriptive research through qualitative analysis in the Integrated Science Laboratory with the precipitation technique. Three samples of iced tea drinks and one positive control sample (with cyclamate added) were analyzed by adding barium chloride (BaCl2) reagent in an acidic atmosphere, with concentrations of 10% and 30%, respectively. The test results showed that one of the samples, iced tea sample RY, formed a white precipitate, indicating the presence of cyclamates, where 30% BaCl₂ produced more precipitate than 10% BaCl₂. This finding suggests that precipitation techniques with higher concentrations of BaCl₂ can improve the visibility of cyclamate detection. However, it should be noted that increasing the concentration of BaCl₂ is not always directly proportional to the identification quality because too high a concentration can cause interference and interfere with the clarity of the observation results.